Giant Cell Tumor of Triquetrum: A Case Report with Literature Review - Ansari, Mohammed T.; Digge, Vijay K.; Mahmood, Asjad (Journal of Wrist Surgery, 2020)
Background Giant cell tumor (GCT) of bone is a benign, aggressive tumor of bone and occurs commonly around the knee and distal radius. GCT of bone rarely occurs in hand. In hand, metacarpals are the most common site and there have been only a few case reports of GCT of the carpal bone. In hand, these tumors are very aggressive and these have a high tendency to recur after intralesional curettage. No long-term study is available for choosing an appropriate method of treatment for these tumors in hand.Case Description Herein, we report a case of GCT of the bone involving triquetrum which was managed by excision of triquetrum and scaphoid bone. The reconstruction of the wrist was done through limited carpal fusion, by doing three corner fusion of the wrist. At 2 years after surgery, the patient was asymptomatic and radiographs revealed fusion of lunocapitate and lunohamate joints with no evidence of recurrence.Literature review Current literature regarding GCT of triquetrum includes case reports that are reviewed in this report.Clinical Relevance This case illustrates the successful treatment of GCT of triquetrum, which is a rare tumor. Three-corner fusion is a reliable and reproducible procedure that has been used for other arthritic conditions. The use of three corner fusion procedure can be extended to GCT of carpal bones. It has been a motion-preserving alternative to proximal row carpectomy.
Keywords: giant cell tumor; triquetrum; carpal; limited carpal fusion